Contrasting patterns of altitudinal distribution between parasitoid wasps of the subfamilies Braconinae and Doryctinae (Hymenoptera: Braconidae). Issue 3 (16th September 2017) - Aguirre, Helmuth; Shaw, Scott R.; Rodríguez‐Jiménez, Andrea
Abstract: Many tropical organisms have narrow altitudinal ranges and therefore may be especially vulnerable to climate change. Parasitoid wasps are no exception, so baseline knowledge about their vulnerability to rising temperatures needs to include analyses of their distributional ranges along elevational gradients. Using museum collections of the parasitoid subfamilies Braconinae and Doryctinae (Hymenoptera: Braconidae) from Costa Rica, we tested two alternative hypotheses explaining altitudinal distributions of communities: (i) the Mid‐domain effect, which states that species diversity peaks at middle elevations as a result of species' random distributions; and (ii) Rapoport's effect, which predicts that species diversity should monotonically decrease with increasing elevation. We found that for the Doryctinae, species diversity decreased monotonically with elevation, while the Braconinae showed two peaks. Species altitudinal ranges increased with elevation in the Doryctinae, as predicted by Rapoport's effect, but not so in the Braconinae. Neither of the subfamilies' distributions fit the prediction of the Mid‐domain effect. The richness peak at low elevations displayed by the Braconinae and Doryctinae matches the distribution of wood‐boring beetles, which are potential hosts for both taxa. The second peak described in the Braconinae at middle elevations may reflect either better access or higher availability of potential hosts in the Diptera and Lepidoptera at those elevations. Because species in the Doryctinae, on average, had altitudinal ranges that were broader and lower in elevation than species in the Braconinae, our results suggest that species in the Doryctinae might have greater resilience to future temperature increases.